2019
DOI: 10.3390/ijerph17010190
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Air Filters Using Natural Sea Salt Particles for Deactivating Airborne Bacterial Particles

Abstract: We developed an antimicrobial air filter using natural sea salt (NSS) particles. Airborne NSS particles were produced via an aerosol process and were continuously coated onto the surface of an air filter under various deposition times. The filtration efficiency and bactericidal performance of the NSS-coated filter against aerosolized bacterial particles (Staphylococcus epidermidis, Escherichia coli) were evaluated quantitatively. The filtration efficiency of the tested filter ranged from 95% to 99% depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Other studies examined the association between SH and microvascular complications including renal manifestations 20 , 21 . Recently, a study was published using data from the Taiwan NHI database, and the authors suggested an association between SH and ESRD 22 . However, this study did not adjust for various confounding factors such as levels of fasting plasma glucose or LDL-cholesterol, and furthermore, their study did not perform sensitivity analyses in the various subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies examined the association between SH and microvascular complications including renal manifestations 20 , 21 . Recently, a study was published using data from the Taiwan NHI database, and the authors suggested an association between SH and ESRD 22 . However, this study did not adjust for various confounding factors such as levels of fasting plasma glucose or LDL-cholesterol, and furthermore, their study did not perform sensitivity analyses in the various subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…The observation about moisture and viral persistence has then been exploited to develop a prototype virus deactivation system using sodium chloride salt impregnated into surgical masks; 100 while the basic principle of sea salt impregnated air filters has been developed for deactivating bacteria. 101 The reason this works is that the viability of an airborne virus is mediated by the salt concentration within droplets and similarly, sodium chloride is a well-known antifungal agent that changes osmoregulation in the cell. Hence salts cause virus inactivation by crystal formation, or cell dysregulation with respect to fungi; both of which may be aspects of aerosol transmission of infection.…”
Section: Infection Control Strategiesmentioning
confidence: 99%
“…However, because of its low flow resistance, it consumes less power per unit of clean air delivered compared to filtration [3]. Filters made of anti-bacterial fibers have also been developed [15,16,17,18,19,20] but their performance remains be proven under realistic indoor conditions. Bactericidal gas spraying, UVGI, plasma discharge and PCO are microbicidal technologies.…”
Section: Introductionmentioning
confidence: 99%